Interior planting - Center for Environmental Design Education and Research (U.S.) (Reston, Va. : Distributed by the Environmental Design Press, 1978)
Presents the concept of plants indoor, plants as a part of interior design, the scale of plant usage and planting as a design element.
Keywords: House plants in interior decoration; Interior decoration